Influences of partial components in firefighters’ personal protective equipment on subjective perception - Kim, Siyeon; Jang, Young Joon; Baek, Yoon Jeong; Lee, Joo-Young (Fashion and textiles, 2014)
The purpose of the present study was to investigate the influences of partial components of firefighters’ personal protective equipment (PPE) on subjective perception during exercise and recovery at 28°C, 40% RH. Eight firefighters participated in eight conditions consisting of various combinations of PPE components weighing from 7.8 to 14.9 kg (fully equipped with all PPE, FullPPE; FullPPE without a self-contained breathing apparatus, NoSCBA; FullPPE without a helmet, NoHelmet; FullPPE without gloves, NoGloves; FullPPE without boots, NoBoots; Full PPE without bunker jacket or pants, NoJP; Not equipped with a helmet, gloves, boots, or breathing apparatus, NoHGBS and Control (1.1 kg; wearing shorts, long-sleeved shirts and long pants)). The results showed: 1) Alleviation of subjectively perceived strain was significantly greater in NoJP during both exercise and recovery than NoHelmet and Nogloves, while the NoJP showed no significant difference with NoBoots and NoHGBS. 2) NoBoots was significantly effective in relieving physiological thermal burden rather than in psychological strain. 3) Exposing the hands and feet affected the local thermal sensation and sweat sensation of the hands and feet, respectively, while exposing the head did not affect local head thermal sensation and sweat sensation. 4) The relationship between clothing microclimate humidity and sweat sensation showed a logarithmic function. The present study indicate that weight loss in boots alleviated physiological strain during exercise, whereas after exercise, doffing jacket and taking off gloves, boots, and helmet simultaneously were both most effective way to relieve thermal strain quickly.